ENVIRONMENTAL BENIGN ROUTE IN THE SYNTHESIS OF PALLADIUM NANOPARTICLES USING LEAVES OF ACALYPHA INDICA L. - MALATHI R.,; GANESAN V, (International Journal of Pharma and Bio Sciences, 2015)
We report the environmental benign route in the synthesis of palladium nanoparticles using the aqueous leaf broth of Acalypha indica L. In this protocol, the biomolecules present in the leaf broth, reduced palladium ions into palladium nanoparticles and these biomolecules also acted as capping and stabilizing agents. The colour change in the reaction medium from pale yellow to dark brown during the incubation period indicated the synthesis of palladium nanoparticles. Further, we used the following analyses to characterize the palladium nanoparticles- UV-Visible spectroscopy, X-ray diffraction patterns (XRD), Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray (EDX) patterns. This protocol of synthesis of palladium nanoparticles using leaf broth of Acalypha indica L. becomes environmental benign route, simple, cost effective as it does not involve any toxic chemicals. Hence, this green approach of this method makes it as an alternative route to physical and chemical methods.